CCN2/CTGF—A Modulator of the Optic Nerve Head Astrocyte - Dillinger, Andrea E.; Weber, Gregor R.; Mayer, Matthias; Schneider, Magdalena; Göppner, Corinna; Ohlmann, Andreas; Shamonin, Mikhail; Monkman, Gareth J.; Fuchshofer, Rudolf (Frontiers in Cell and Developmental Biology, 2022)
In primary open-angle glaucoma (POAG), a neurodegenerative disease of the optic nerve (ON) and leading cause of blindness, the optic nerve head (ONH) undergoes marked structural extracellular matrix (ECM) changes, which contribute to its permanent deformation and to degeneration of ON axons. The remodeling process of the ECM causes changes in the biomechanical properties of the ONH and the peripapillary sclera, which is accompanied by an increased reactivity of the resident astrocytes. The molecular factors involved in the remodeling process belong to the transforming growth factor (TGF)-β superfamily, especially TGF-β2. In previous publications we showed that TGF-β2 induced ECM alterations are mediated by Cellular communication network factor (CCN)2/Connective Tissue Growth Factor (CTGF) and recently we showed that CCN2/CTGF is expressed by astrocytes of the ON under normal conditions. In this study we wanted to get a better understanding of the function of CCN2/CTGF under normal and pathologic conditions. To this end, we analyzed the glial lamina and peripapillary sclera of CCN2/CTGF overexpressing mice and studied the effect of CCN2/CTGF and increasing substratum stiffness on murine ON astrocytes in vitro. We observed enhanced astrocyte reactivity in the ONH, increased ECM protein synthesis in the peripapillary sclera and increased Ccn2/Ctgf expression in the ONH during the pathologic development in situ. CCN2/CTGF treatment of primary murine ON astrocytes induced a higher migration rate, and increase of ECM proteins including fibronectin, elastin and collagen type III. Furthermore, the astrocytes responded to stiffer substratum with increased glial fibrillary acidic protein, vimentin, actin and CCN2/CTGF synthesis. Finally, we observed the reinforced appearance of CCN2/CTGF in the lamina cribrosa of glaucomatous patients. We conclude that reactive changes in ONH astrocytes, induced by the altered biomechanical characteristics of the region, give rise to a self-amplifying process that includes increased TGF-β2/CCN2/CTGF signaling and leads to the synthesis of ECM molecules and cytoskeleton proteins, a process that in turn augments the stiffness at the ONH. Such a scenario may finally result in a vicious circle in the pathogenesis of POAG. The transgenic CTGF-overexpressing mouse model might be an optimal model to study the chronic pathological POAG changes in the ONH.